THE IMPACT OF INDUSTRIAL REVOLUTION TOWARDS CHILDREN AS REFLECTED IN CHARLES DICKENS’ OLIVER TWIST - Lusianus Laia; Merri Hotnauli Siregar; Gongsar Silaban (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2022)
This study deals with The Impact of Industrial Revolution towards Children as reflected in Charles Dickens’ Oliver Twist. The aim of this study is to find out the negative impact of industrial revolution towards children and how these negative impacts affect children. This study uses qualitative research method and sociology theory of literature in analyzingthe data relates to the description of the negative impact of industrial revolution and how these negative impacts of industrial revolution affect children as portrayed in Charles Dickens' Oliver Twist. The result of this analysis shows that there are two negative impacts of the industrial revolution toward children in Charles Dickens’ Oliver Twist, namely Poverty and Child Labor. Meanwhile, how do these negative impacts of the industrial revolution affect children there are four types, they are: Children Recruitment as Criminals, Baby Farming, Children Apprentices and Physical Abuse towards Children.